Aging hardening and precipitation behavior of Fe-31.6Mn-8.8Al-1.38C austenitic cast steel. (November 2020) - Feng, Yifan; Song, Renbo; Wang, Yongjin; Liu, Ming; Li, Hong; Liu, Xingang
Abstract: The aging hardening and precipitation behavior of Fe-31.6Mn-8.8Al-1.38C austenitic cast steel under aging heat treatment were investigated by microstructures characterization and hardness tests. The as-quenched samples were aged at 550 °C, 700 °C, 800 °C and 900 °C for various time. After aging at 550 °C, the hardness exhibited a continuous increase and finally stabilized around 480 HB, meanwhile, the β-Mn phase nucleated at austenite grain boundaries without accompanied with α-precipitate, which is mainly related to the nano-sized κ′-carbides. When aging was conducted at 700 °C and 800 °C, the hardness was only stable at 320HB because of α precipitation and high temperature softening, and the β-Mn phase appeared through the decomposition of γ → α. According to the results of nano-indentation tests, the austenite matrix exhibited relatively low nano-hardness of the sample aged at 800 °C than that of 550 °C, due to the precipitation of micron-sized κ′-carbides. In addition, considering the size, morphology and distribution of κ phase after different aging treatments, four types of that were described in the present study. Graphical abstract: Image 1 Highlights: Four types of κ-carbides were described after aging processes (550 °C–900 °C). Nano-sized κ-carbides can promote the precipitation of β-Mn without α-precipitate. The nano-hardness of austenite matrix was obtained by nano-indentation.